Islamic Religious Education Learning Model in Shaping the Character of SDN 9 Meurah Mulia Students, North Aceh Regency - Muhammad Fuadi; Azhar Azhar (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the PAI Learning Model in Shaping the Character of SD 9 Meurah Mulia Students. The method used is a qualitative method with a descriptive approach. The study subjects included the principal, PAI teachers, and several students. The results of this study describe. Islamic Religious Education Learning Model in Shaping student character using tazkirah, encouragement, repetition, and reminding models. Make a match, a learning model such as discovery (Inquiry) in knowing the evidence of the power of Allah SWT as the teaching material is understanding the meaning in Asmaul husna, presenting angels in his daily life. For moral learning, a role-playing learning model can be used. A learning model (NHT) can be used to learn the history of Islamic culture. Then the Islamic values taught to students in forming a noble character are Islamic values combined with morals, which is essential because it is one of the school's goals. Applying Islamic values in shaping students' personalities, reading and eating asmaul husna is carried out every morning before entering class, which is accompanied by all students and educators. The obstacles faced in implementing Islamic values in shaping student character are the involvement of student guardians who do not pay attention, family, social environment, economic conditions, and exit environment.